2020
DOI: 10.1101/2020.07.06.188920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Revisiting the carbon isotope discrimination and water use efficiency relation: the influence of mesophyll conductance

Abstract: SummaryThe carbon isotope discrimination (Δ) has been used widely to infer intrinsic water-use efficiency (iWUE) of C3 plants, a key parameter linking carbon and water fluxes. Despite the essential role of mesophyll conductance (gm) in photosynthesis and Δ, its effect on Δ-based predictions of iWUE has generally been neglected. Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…A recent study by Ma et al . (2020) demonstrated that the ternary effect on iWUE Δ was small ( c . 1% error).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Ma et al . (2020) demonstrated that the ternary effect on iWUE Δ was small ( c . 1% error).…”
Section: Discussionmentioning
confidence: 99%
“…These factors are ternary effects and respiratory and photorespiratory fractionations. A recent study by Ma et al (2020) demonstrated that the ternary effect on iWUE Δ was small (c. 1% error). Our measurements for iWUE analyses occurred when light intensity was above 800 μmol mol −1 , and under these conditions the whole-tree 13 C-discrimination would have been largely dominated by photosynthesis (Drake et al, 2016).…”
Section: Whole-tree Mesophyll Conductance (G M )mentioning
confidence: 95%